THE INFLUENCE OF INTELLIGENCE QUOTIENT AND EMOTIONAL QUOTIENT ON THE TENTH GRADE STUDENTS’ ENGLISH ACHIEVEMENT OF STATE SENIOR HIGH SCHOOL 6 OF PALEMBANG - Hartati, Sri (Universitas Muhammadiyah Palembang, 2018)
This study aimed for finding out whether or not (1) there is a significant influence of intelligence quotient on students’ English achievement; (2) there is a significant influence of emotional quotient on students’ English achievement; (3) there is a significant influence of intelligence quotient and emotional quotient on students’ English achievement. The population of this study consisted of 223 students of the tenth grade student of senior high school 6 of Palembang. The sample was selected by using simple random sampling. The data were collected by using documentation, questionnaire, and tests. The data were analyzed by using descriptive statistic and inferential statistic (correlation and regression analyses), F-test for multiple correlation and t-test for partial correlation, significant 95% (0.05) by SPSS version 15. The result showed that there was a low correlation of intelligence quotient on students’ English achievement (r=0.364); there was a low correlation of emotional quotient on students’ English achievement (r=0.368); there was an enough correlation of intelligence quotient and emotional quotient on students’ English achievement (r=0.468). The influence of intelligence quotient was 0.133 (13.3%) on students’ English achievement. The influence of emotional quotient was 0.136 (13.6%) on students’ English achievement. The influence of intelligence quotient and emotional quotient were 0.219 (21.9%) on students’ English achievement. The variability of students’ English achievement could be explained 21.9% by intelligence quotient and emotional quotient. The rest (78.1%) was determined by other factors.